Effect of working length determination methods on postoperative pain after root canal treatment: a systematic review and meta-analysis - Kumar, Gaurav; Mohan, Sumit; Viswanath, Butta; Priyank, Harsh (Journal of dental anesthesia and pain medicine: JDAPM, 2025)
This systematic review aimed to assess the effect of various working length determination methods on the incidence of postoperative pain after root canal treatment. A comprehensive literature search was conducted across three electronic databases to identify randomized clinical trials. Two reviewers independently screened the articles, extracted relevant data, and assessed methodological quality using the Cochrane risk-of-bias assessment tool. For quantitative synthesis, a random-effects model was employed to compute the pooled mean difference by comparing the simultaneous and separate working-length determination methods. Sensitivity analyses were conducted after excluding studies that contributed disproportionately to overall heterogeneity. Seven studies met the criteria for qualitative review and three were included in the meta-analysis. The findings suggest that simultaneous determination of working length using integrated electronic apex locators may offer an advantage in reducing postoperative pain. However, this interpretation is limited by the substantial heterogeneity observed across the included studies. This review highlights the necessity for robust and well-designed clinical trials with large sample sizes and standardized protocols to obtain conclusive evidence.